Oral health behavior differences between dental students in graduate and doctoral programs - Senem Ünver; Seçil Karakoca Nemli̇; Nuran Özyemi̇şci̇ Cebeci̇ (Istanbul University, 2018)
DOI: 10.26650/eor.2018.80220Purpose This study aimed to compare oral health behavior between dental students in graduate programs and those in doctoral programs (PhD students) and determine the effects of parental education and occupation on these behaviors. Materials and Methods A questionnaire on oral health behaviors was distributed in a faculty of dentistry in Ankara, Turkey. A total of 629 questionnaires were distributed, and 528 dental graduate and 101 PhD students responded. Parental education and occupation were also recorded, and data were statistically analyzed. Results Statistically significant differences were found between the two groups with respect to the frequency of replacing toothbrush (p=0.001), use of electric toothbrush (p<0.001), frequency of brushing (p<0.001), amount of water used to rinse mouth (p<0.001), toothpaste selection criteria (p<0.001), use of dental floss (p<0.001), amount of toothpaste used for brushing (p=0.018), frequency of professional care (p<0.001), and sugar consumption (p<0.001). The PhD group showed more favorable outcomes for these behaviors except for toothpaste selection. Parental education and occupation were correlated with higher frequencies of flossing and mouth rinsing. Conclusion The outcomes of this study show that the self-reported quality of overall oral health behavior is more pronounced in PhD students than in graduate students, with the exceptions of behaviors regarding the duration of brushing, toothpaste selection criteria, and use of mouth rinse. The current dental curriculum in the universities should be revisited with respect to oral health attitudes. This study also implies that educational and occupational status of parents had little effect on oral health behavior of the students, including the use of dental floss and mouth rinse.